2006
DOI: 10.1109/iccad.2006.320096
|View full text |Cite
|
Sign up to set email alerts
|

Using CAD to Shape Experiments in Molecular QCA

Abstract: This paper examines how circuits and systems made from molecular QCA devices might function. Our design constraints are "chemically reasonable" in that we consider the characteristics and dimensions of devices and scaffoldings (circuit boards to attach devices to) that have actually been fabricated (currently in isolation). We will show that not only is the work presented here a necessary first step for any work in QCA CAD, but also that by considering issues related to design can actually help shape experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Similar functionality will also be needed as more complex NML circuits are designed and fabricated. However, existing work [45] has suggested that, for QCA-like architectures (that require nearest neighbor interactions) while theoretically possible, wire crossings like those illustrated in figure 9(a) can be more difficult to physically implement than in a CMOS equivalent. Given the experimental state of the art for most electrostatic implementations of QCA, any such crossing would seemingly need to be done in-plane.…”
Section: Local Interconnectmentioning
confidence: 99%
“…Similar functionality will also be needed as more complex NML circuits are designed and fabricated. However, existing work [45] has suggested that, for QCA-like architectures (that require nearest neighbor interactions) while theoretically possible, wire crossings like those illustrated in figure 9(a) can be more difficult to physically implement than in a CMOS equivalent. Given the experimental state of the art for most electrostatic implementations of QCA, any such crossing would seemingly need to be done in-plane.…”
Section: Local Interconnectmentioning
confidence: 99%
“…In QCA research, similar studies have been done. From reconfigurable designs ] and defect studies Ottavi et al 2005;Niemier et al 2006] up to fault modeling [Huang et al 2004;Crocker et al 2007] and this work on mapping, QCA is proving to be an exciting emerging technology with several implementation alternatives that target many applications.…”
Section: Discussionmentioning
confidence: 99%
“…Proper association of defects to faults helps in studying the fault probabilities and yield. By examining experimental data and performing simulations at the physical level Niemier et al 2006;Donahue and Porter], we have matched defects to faults for two QCA implementations. In Table I, we summarize the faults that are induced by five typical defect types, that is, shifts, rotations, missing, stray charges and misshapenness.…”
Section: Qca Defects and Faultsmentioning
confidence: 99%
“…-did not consider the overhead of clocking, which is required to drive any QCA-based computation; -looked at electrostatic implementations of QCA, which inherently limit application spaces (e.g., due to low operating temperatures [Amlani et al 1999]); -looked at a molecular implementation [Qi et al 2003], for which there is no proven device that can be deterministically placed-and where functional correctness will be subject to small placement variations, stray charges, and so on [Niemier et al 2006]. …”
Section: Introductionmentioning
confidence: 99%